Seafood Processing, Preservation, and Analytical Techniques in the Age of Industry 4.0 - Abdo Hassoun; Shahida Anusha Siddiqui; Slim Smaoui; İlknur Ucak; Rai Naveed Arshad; Paula Garcia-Oliveira; Miguel A. Prieto; Abderrahmane Aït-Kaddour; Rosa Perestrelo; José S. Câmara; Gioacchino Bono (Applied Sciences, 2022)
Fish and other seafood products are essential dietary components that are highly appreciated and consumed worldwide. However, the high perishability of these products has driven the development of a wide range of processing, preservation, and analytical techniques. This development has been accelerated in recent years with the advent of the fourth industrial revolution (Industry 4.0) technologies, digitally transforming almost every industry, including the food and seafood industry. The purpose of this review paper is to provide an updated overview of recent thermal and nonthermal processing and preservation technologies, as well as advanced analytical techniques used in the seafood industry. A special focus will be given to the role of different Industry 4.0 technologies to achieve smart seafood manufacturing, with high automation and digitalization. The literature discussed in this work showed that emerging technologies (e.g., ohmic heating, pulsed electric field, high pressure processing, nanotechnology, advanced mass spectrometry and spectroscopic techniques, and hyperspectral imaging sensors) are key elements in industrial revolutions not only in the seafood industry but also in all food industry sectors. More research is still needed to explore how to harness the Industry 4.0 innovations in order to achieve a green transition toward more profitable and sustainable food production systems.